Effects of Different Ligands in the Notch Signaling Pathway on the Proliferation and Transdifferentiation of Primary Type II Alveolar Epithelial Cells - Liu, Xiuxiang; Zhu, Xiaoxi; Zhu, Guoqing; Wang, Chaoyun; Gao, Ruiwei; Ma, Jinshuai (Frontiers in Pediatrics, 2020)
Background: Transdifferentiation of type II alveolar epithelial cells (AECII) into type I alveolar epithelial cells (AECI) is involved in neonatal respiratory distress syndrome (NRDS). Different ligands of the Notch pathway could have different effects on AECII transdifferentiation. Objective: To investigate the effects of Dlk1 and Jagged1 on the proliferation and transdifferentiation of AECII. Methods: Fetal AECIIs (19 days of gestation) were divided: control group, Dlk1 group, rhNF-κB group. Proliferation was tested using the MTT assay. Expression of surfactant protein C (SP-C) and aquaporin 5 (AQP5) was examined by immunofluorescence. mRNA and protein levels of SP-C, AQP5, Nortch1, Dlk1, Jagged1, and Hes1 were examined by RT-PCR and western blot. Results: In response to Dlk1, cell number and proliferation were increased (P < 0.05), and mRNA and protein levels of SP-C, Dlk1, Notch1, and Hes1 were up-regulated, while AQP and Jagged1 were decreased. In response to rhNF-κB, the cell number and proliferation were reduced, and mRNA and protein levels of Jagged1 and Notch1 were up-regulated, while Dlk1, and SP-C were downregulated. In the Dlk1 group, SP-C, and AQP5 expression patterns suggested that the cells were still transdifferentiating by 96 h, while in the rhNF-κB group, most cells had transdifferentiated by 72 h and were close to apoptosis by 96 h. Conclusion: These results suggest that Dlk1 promoted proliferation of AECIIs and inhibited cell transdifferentiation, while Jagged1 treatment inhibited proliferation of AECIIs and promoted transdifferentiation to AECIs. These results provide some clue for the eventual management of NDRS.